New verbs and dictionaries: A method for the automatic detection of neology in Spanish verbs. (20th June 2021) - Castro, Ana; Nazar, Rogelio; Renau, Irene
Abstract: The appearance of new verbs can be observed regularly, but verbs are not frequently investigated in neology, and they are difficult to detect automatically. In this study, a corpus-based method is proposed to detect Spanish verbs with a series of algorithms that analyse the morphology of regular verbs. The vocabulary was drawn from a large corpus and contrasted with a major dictionary of Spanish. Then, a series of filters were applied to distinguish between valid neologism candidates and spelling mistakes. Around 88% of the neologisms proposed by the method were correct and we estimate that the system detected 76% of the neologisms present in the corpus. This procedure can be included in the workflow of a lexicographic project as a regular part of the task, as a systematic way of collecting new verbs from the data and avoiding under-representation or bias.